Temporally-oriented possession: A corpus for tracking possession over time - Dhivya I Chinnappa; Alexis Palmer; Eduardo Blanco (Society for Computation in Linguistics, 2019)
This abstract presents a new corpus for temporally-oriented possession or tracking concrete objects as they change hands over time. We annotate Wikipedia articles for 90 different well-known artifacts (paintings, diamonds, and archaeological artifacts), producing 799 artifact-possessor relations covering 735 unique possessors. Each possession relation is annotated with features capturing duration of possession, as well as the certainty of the possession according to textual evidence. A possession timeline is then produced for each artifact. This corpus provides a foundation for analysis of temporally-oriented possession, as well as work on automatic production of possession timelines.
Keywords: possession; timeline; temporal anchor